Analisis Pengaruh Work Life Balance, Pengembangan Karir, Motivasi Kerja Dan Disiplin Kerja Terhadap Kepuasan Kerja Pegawai Pada Dinas Perdagangan Dan Perindustrian Kabupaten Labuhanbatu - Simamora, Asrani Juni (Universitas Labuhanbatu, 2021)
This study aims to determine the analysis of the influence of work life balance, work discipline, work motivation and work discipline on job satisfaction in the National Trade and industry Labuhanbatu. In testing individually / partially (t test) obtained four variables have a significant influence on job satisfaction. Where the value of the significant probability variable work life balance (X1) is less than 0.05, which is equal to 0.026 with a value of beta ( ③ ) of 0.473, for the variable work discipline (X2) is less than 0.05, which is equal to 0.005 with a value of beta ( ③ ) of 0.056, variable work motivation (X3) has a significant probability value of more than 0.05, which is equal to 0.020 with a value of beta ( ③ ) of 0.223, as well as the variable work discipline (X4) has a significant probability value of more than 0.05 that is equal to 0.018 with a beta value of 0.285. For the results of the analysis test based on the F test conducted showed that work life balance, work discipline, work motivation and work discipline simultaneously or together have a significant positive influence on job satisfaction in the Labuhanbatu Regency market.